GLAST Deficiency in Mice Exacerbates Gap Detection Deficits in a Model of Salicylate-Induced Tinnitus - Yu, Hong; Vikhe Patil, Kim; Han, Chul; Fabella, Brian; Canlon, Barbara; Someya, Shinichi; Cederroth, Christopher R. (Frontiers in Behavioral Neuroscience, 2016)
Gap detection or gap pre-pulse inhibition of the acoustic startle (GPIAS) has been successfully used in rat and guinea pig models of tinnitus, yet this system has been proven to have low efficacy in CBA mice, with low basal GPIAS and subtle tinnitus-like effects. Here, we tested five mouse strains (CBA, BalbC, CD-1, C57BL/6 and 129sv) for pre-pulse inhibition (PPI) and gap detection with varying interstimulus intervals (ISI) and found that mice from a CBA genetic background had the poorest capacities of suppressing the startle response in the presence of a pre-pulse or a gap. CD-1 mice displayed variable responses throughout all ISI. Interestingly, C57BL/6, 129sv and BalbC showed efficient suppression with either pre-pulses or gaps with shorter ISI. The glutamate aspartate transporter (GLAST) is expressed in support cells from the cochlea and buffers the excess of glutamate. We hypothesized that loss of GLAST function could sensitize the ear to tinnitus-inducing agents, such as salicylate. Using shorter ISI to obtain a greater dynamic range to assess tinnitus-like effects, we found that disruption of gap detection by salicylate was exacerbated across various intensities of a 32-kHz narrow band noise gap carrier in GLAST knockout (KO) mice when compared to their wild-type (WT) littermates. Auditory brainstem responses (ABR) and distortion-product otoacoustic emission (DPOAE) were performed to evaluate the effects on hearing functions. Salicylate caused greater auditory threshold shifts (near 15 dB) in GLAST KO mice than in WT mice across all tested frequencies, despite similarly reduced DPOAE. Despite these changes, inhibition using broad-band gap carriers and 32 kHz pre-pulses were not affected. Our study suggests that GLAST deficiency could become a useful experimental model to decipher the mechanisms underlying drug-induced tinnitus. Future studies addressing the neurological correlates of tinnitus in this model could provide additional insights into the mechanisms of tinnitus.